Target modal split model - Basarić, Valentina; Jović, Jadranka (Transport, 2011)
The research presented in this paper is aimed at defining a model that enables the management of the relationship between private vehicles and public transport applying the available instruments of city transport policy such as parking policy and public transport policy measures. Statistical data used for modelling is sourced from the database in a wide range of EU cities. The target model was developed in the form of stepwise regression analysis. Very favourable statistical results were obtained, and the subsequent tests on the city of Novi Sad (250000 inhabitants) led to the conclusion that the obtained results were suitable for implementation in practice. The results of the implemented procedure are of great importance for the enhancement of the existing transport policies in cities, as they enable the development of strategies for finding combinations of instruments that would bring the transport system and urban environment into a desired-viable rather than consequential condition.First Published Online: 09 Jan 2012